Whole-Genome Sequencing Analysis of Non-Typhoidal Salmonella Isolated from Breeder Poultry Farm Sources in China, 2020-2021 - Zijing Ju; Lulu Cui; Changwei Lei; Mengze Song; Xuan Chen; Ziwei Liao; Tiejun Zhang; Hongning Wang (MDPI AG, 2023)
Non-typhoidal salmonellosis is a dangerous foodborne disease that causes enormous economic loss and threatens public health worldwide. The consumption of food, especially poultry or poultry products, contaminated with non-typhoidal Salmonella (NTS) is the main cause of human salmonellosis. To date, no research has identified the molecular epidemiological characteristics of NTS strains isolated from breeder chicken farms in different provinces of China. In our study, we investigated the antimicrobial resistance, phylogenetic relationships, presence of antimicrobial resistance and virulence genes, and plasmids of NTS isolates recovered from breeder chicken farms in five provinces of China between 2020 and 2021 by using a whole-genome sequencing (WGS) approach and phenotypic methods. All sequenced isolates belonged to six serovars with seven sequence types. Nearly half of the isolates (44.87%) showed phenotypic resistance to at least three classes of antimicrobials. Salmonella enterica serotype Kentucky harbored more antimicrobial resistance genes than the others, which was highly consistent with phenotypic resistance. Furthermore, the carried rate of 104 out of 135 detected virulence genes was 100%. Overall, our WGS results highlight the need for the continuous monitoring of, and additional studies on, the antimicrobial resistance of NTS.